HIV self-testing acceptability among injured persons seeking emergency care in Nairobi, Kenya - Adam R. Aluisio; Scarlett J. Bergam; Janet Sugut; John Kinuthia; Rose Bosire; Eric Ochola; Beatrice Ngila; Kate M. Guthrie; Tao Liu; Mary Mugambi; David A. Katz; Carey Farquhar; et al. (Taylor & Francis Group, 2023)
Background Emergency department-based HIV self-testing (ED-HIVST) could increase HIV-testing services to high-risk, under-reached populations. Objectives This study sought to understand the injury patient acceptability of ED-HIVST. Methods Injury patients presenting to the Kenyatta National Hospital Accident and Emergency Department were enrolled from March to May 2021. Likert item data on HIVST assessing domains of general acceptability, personal acceptability, and acceptability to distribute to social and/or sexual networks were collected. Ordinal regression was performed yielding adjusted odds ratios (aOR) to identify characteristics associated with high HIVST acceptability across domains. Results Of 600 participants, 88.7% were male, and the median age was 29. Half reported having primary care providers (PCPs) and 86.2% reported prior HIV testing. For each Likert item, an average of 63.5% of the participants reported they 'Agree Completely' with positive statements about ED-HIVST in general, for themselves, and for others. In adjusted analysis for general acceptability, those <25 (aOR = 1.67, 95%CI:1.36-2.08) and with prior HIV testing (aOR = 1.68, 95%CI:1.27-2.21) had greater odds of agreeing completely. For personal acceptability, those with a PCP (aOR = 3.31, 95%CI:2.72-4.03) and prior HIV testing (aOR = 1.83, 95%CI:1.41-2.38) had greater odds of agreeing completely. For distribution acceptability, participants with a PCP (aOR = 2.42, 95%CI:2.01-2.92) and prior HIV testing (aOR = 1.79, 95%CI: 1.38-2.33) had greater odds of agreeing completely. Conclusions ED-HIVST is perceived as highly acceptable, and young people with prior testing and PCPs had significantly greater favourability. These data provide a foundation for ED-HIVST programme development in Kenya.